Ensuring Economic and Food Security through the Development of the Agricultural Sector (The (Example of Ukraine) - KARINA, UTENKOVA; ANDRII, DUKHNEVYCH; BORYS, POHRISHCUK; LIUDMYLA, BEREZINA; BOHDAN, BRATANOV (The journal of contemporary issues in business and government, 2020)
The purpose of the academic paper is to develop ways in order to increase the level of food security of Ukraine and the world on the basis of sustainable development by providing a bioeconomic vector of development of the agricultural sector. Research methods: analysis of theoretical and empirical scientific papers, analytical reports, policy papers, synthesis, induction, SWOT-analysis. Results: as a result of the study conducted, a bioeconomic model of agricultural sector development has been developed on the basis of sustainable intensification, the application of which will ensure the required level of food security in Ukraine and the world. The model includes a number of aspects for its application in different operating conditions. Conclusions: Ireland, Austria and France are the leaders in the field of food security according to the Global Food Security Index (GFSI). In Ukraine, this index has the lowest value among the studied countries. Ukraine’s food security is affected by such negative factors as underdeveloped infrastructure, lack of funding, and lack of a strategic vision of food security at the state level. At the same time, there is a great untapped potential in agricultural production in Ukraine. The developed theoretical bioeconomic model of agricultural development includes the maximum number of factors that affect the quality and stability of production, storage, and minimizes the negative effects of production. It has been taken into account that the long-term ability of the food system for provision of sufficient nutritious food will depend on its ability to respond to environmental and social-economic challenges, minimizing the negative impact on human health and the environment. The SWOT-analysis of the developed model has been carried out, which includes the analysis of benefits and shortcomings, opportunities and challenges as a result of its application. The developed bioeconomic model of agricultural sector development will contribute to solving a wide range of topical issues of economic and food security of Ukraine and the world.